2021
DOI: 10.1016/s2352-4642(21)00270-4
|View full text |Cite|
|
Sign up to set email alerts
|

Infliximab versus second intravenous immunoglobulin for treatment of resistant Kawasaki disease in the USA (KIDCARE): a randomised, multicentre comparative effectiveness trial

Abstract: Background Although intravenous immunoglobulin (IVIG) is effective therapy for Kawasaki disease, 10-20% of patients have recrudescent fever as a sign of persistent inflammation and require additional treatment. We aimed to compare infliximab with a second infusion of IVIG for treatment of resistant Kawasaki disease.Methods In this multicentre comparative effectiveness trial, patients (aged 4 weeks to 17 years) with IVIG resistant Kawasaki disease and fever at least 36 h after completion of their first IVIG inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 29 publications
(38 reference statements)
0
33
0
Order By: Relevance
“…Date of onset was defined as the first day of fever and was reported monthly for all patients from 28 institutions participating in the KIDCARE trial. 9 The institutional review board (IRB) at the University of California, San Diego (UCSD; central IRB for trial) and participating sites approved the study. A waiver of informed consent was granted for collection of dates of KD onset because they are not protected health information.…”
Section: Methodsmentioning
confidence: 99%
“…Date of onset was defined as the first day of fever and was reported monthly for all patients from 28 institutions participating in the KIDCARE trial. 9 The institutional review board (IRB) at the University of California, San Diego (UCSD; central IRB for trial) and participating sites approved the study. A waiver of informed consent was granted for collection of dates of KD onset because they are not protected health information.…”
Section: Methodsmentioning
confidence: 99%
“…However, as a conditional recommendation, glucocorticoids are a reasonable alternative (e.g., starting at 2 mg/kg/day and tapering over 15 days or a single dose of 20–30 mg/kg). Repeated doses of IVIG may put patients at risk of hemolytic anemia, and the results of ongoing studies may alter this recommendation in the future (45–47). In patients with risk factors for hemolytic anemia with IVIG, such as non–type O blood groups, alternative therapies, such as glucocorticoids or nonglucocorticoid immunomodulatory therapy, should be considered (45,48).…”
Section: Resultsmentioning
confidence: 99%
“…Youn (2016) reported that the median duration of fever after completion of the first treatment was shorter in the infliximab group compared to the IVIG group (6 hours, IQR 2‐24 hours in the infliximab group and 17 hours, IQR 4‐62.5 hours in the IVIG group; P = .044) 30 . Burns (2021) reported that the mean duration of fever from enrolment was shorter in the infliximab group compared to the IVIG group (infliximab group 1.5 days [SD 1.4], IVIG group 2.5 days [SD 2.5]; P = .014) 31 …”
Section: Resultsmentioning
confidence: 99%